Factors determining household market participation in small ruminant production in the highlands of Ethiopia - Gebremedhin, Berhanu; Hoekstra, Dirk; Tegegne, Azage; Shiferaw, K.; Bogale, A. (International Livestock Research Institute, 2015)
Small ruminants, which account for more than half of the domesticated ruminants in the world, are an important component of the farming systems in most developing countries. Despite their economic and social importance, socioeconomic and marketing research on small ruminants has so far been limited, a fact which also holds strongly true in Ethiopia. This study, based on survey data of 5004 Ethiopian smallholder households, uses analysis of descriptive information and econometric analysis to draw implications to promote market orientation. Econometric results are based on estimation of bivariate, ordinal, and multinomial probit models. We find that herd size, herd structure, access to livestock market, and involvement in the institutional services of extension and credit stand out as the most important factors affecting market participation behaviour of households. Our results imply that an effective package of interventions to promote market-oriented small ruminant production will need to include development of livestock market infrastructure and market institutions, improved access to extension and credit use, efficient animal reproduction and management, and proper animal health care.